Position effect variegation of an acid phosphatase gene in Drosophila melanogaster. - Frisardi, M.C.; MacIntyre, R.J. (Molecular and General Genetics, 1984)
X-ray mutagenesis has produced a series of deficiencies in a duplication of part of the third chromosome containing the acid phosphatase gene (Acph-1) in Drosophila melanogaster. In one of these deficiencies, Acph-1 is shown to be undergoing position effect variegation. Naturally occurring electrophoretic variants of the enzyme were used to visualize and determine quantitatively the extent of variegation of the allele which is cis to the heterochromatic breakpoint. Alteration of genotypic background and temperature provided further evidence for position effect. Rocket immunoelectrophoresis was used to correlate the levels of acid phosphatase activity and protein in flies containing the deficiency. A novel result indicates that the variegation is not the consequence of an averaging of active and inactive cells, but rather due to a quantitative alteration of gene activity within at least some individual cells.